Actions, Products, and Truth-Bearers: A Critique of Twardowskian Accounts. Issue 3 (5th April 2020) - Bronzo, Silver
Abstract: Friederike Moltmann has recently proposed an account of truth-bearers that draws on Kazimierz Twardowski's action/product distinction. Her account is meant to provide a third way between the dominant view of primary truth-bearers as mind-independent entities and the recently revived construal of them as mental or linguistic acts. This paper argues that there is no room for Twardowskian accounts because they are based on a notion of "nonenduring product" that defies comprehension, and no need for them because the linguistic data that Twardowskians take to refute the act-theoretic approach can, in fact, be handled by that approach.